Akibat Hukum Perjanjian Jual Beli Hak Atas Tanah - Made Erik Krismeina Legawantara; Desak Gde Dwi Arini; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2020)
Sale and purchase is usually done by an agreement or what is known as a sale and purchase agreement, based on customary law a sale and purchase agreement is a real agreement, meaning that the delivery of the goods agreed upon is an absolute requirement fulfilled for the existence of an agreement. This research aims to find out about the arrangement of the land purchase agreement and find out the legal consequences of the land purchase agreement if there is a default. The method used in this research is the normative legal method with the statutory approach (satute aproach) and the conceptual approach. There are two types of data used, namely Primary (Laws and Regulations) as primary data and secondary data (sources of literature, books and research journals). Data analyzed are presented in the form of descriptions. Research results show that the sale and purchase rights of land rights are regulated in article 1457. The Civil Code which determines that buying and selling is an agreement between the buyer and the seller in an agreement where the legal terms of the agreement must meet subjective and objective conditions, with the consequence that the agreement is not can be canceled unilaterally because it must be implemented in good faith. Then, due to the Default Law for the Parties In Canceling the Deed of Agreement on the Sale and Purchase of Land Rights, it is regulated in Article 1366 of the Civil Code which stipulates that everyone is responsible not only for losses caused by his actions, but also for losses caused by negligence or indifference careful. Article 1366 of the Civil Code explains the responsibility of someone who has done harm to another person / other party, either because of his own actions or due to negligence and carelessness that causes other parties to suffer losses from him.